Konsep Keadilan bagi Perempuan dalam Poligami dan Monogami dalam Perspektif Fiqih Islam - Ahla Ma’wa Masfufah; Fitri Wulandari; Nazla Nuur Alya Imaniyah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the concept of justice for women in monogamous and polygamous marriage systems from the perspective of Islamic jurisprudence (fiqh). Justice is one of the fundamental principles in Islam, especially in household life, which emphasizes the balance of rights and responsibilities between husband and wife. In practice, monogamy and polygamy have different characteristics and challenges in realizing justice for women. This research uses a qualitative method with a library research approach by examining the Qur’an, Hadith, fiqh literature, and other relevant academic sources. The findings indicate that monogamy is considered simpler in implementing justice because attention, financial support, and affection are more focused on one wife. On the other hand, polygamy is permitted in Islam under the main condition that the husband can act fairly, particularly in terms of financial support, housing, treatment, and time allocation. However, the implementation of justice in polygamy often faces challenges, especially in emotional and psychological aspects that are difficult to balance. From the perspective of Islamic jurisprudence, justice for women is not limited to material fulfillment but also includes respect, protection, and emotional and psychological well-being. Therefore, this study emphasizes that justice is a fundamental foundation in building a harmonious household, both in monogamous and polygamous marriage systems.   Keywords: Justice, Women, Polygamy, Monogamy, Islamic Jurisprudence